A serpent's tooth - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery., 2013)
When a lost Mormon child wanders into Absaroka County, the intrepid Wyoming sheriff teams up with feisty deputy Victoria Moretti and longtime friend Henry Standing Bear on a high plains scavenger hunt that leads them to a violent interstate polygamy group.